Reusability of Immobilized Cells for Subsequent Balsamic-Styled Vinegar Fermentations - Ucrecia F. Hutchinson (Fermentation, 2020)
Cell immobilization is a process augmentation technique aimed at improving microbial survival and activity under stressful conditions. It offers the opportunity to reuse the immobilized cells for several fermentation cycles. The present study investigated the use of recycled cells entrapped in calcium-alginate beads and cells adsorbed on corncobs (CC) and oakwood chips (OWC) in subsequent fermentation cycles for balsamic-styled vinegar (BSV) production. Sugars, pH, alcohol and total acidity were monitored during fermentation. Microbial activity and product formation declined when immobilized cells were reused for the second cycle for CC and OWC fermentations. Recycled cells entrapped in Ca-alginate beads completed the second cycle of fermentations, albeit at reduced acetification rates compared to the first cycle. Scanning electron microscope (SEM) imaging results further showed a substantial the structural integrity loss for Ca-alginate beads after the first cycle, and with minor changes in the structural integrity of CC. The OWC displayed a similar morphological structure before and after the first cycle. The sensory results showed that BSV produced using immobilized cells with Ca-alginate beads and CC was palatable, while those produced using OWC had negative attributes. Ca-alginate beads offered better protection for the fermentation consortium for culture reusability in BSV fermentations.